Obese obstructive sleep apnea patients with tonsil hypertrophy submitted to tonsillectomy - Martinho, Fernanda Louise [UNIFESP] (2006)
The physiopathology of obstructive sleep apnea-hypopnea syndrome (OSAHS) is multifactorial and obesity has been shown to be one of the main factors correlated with its occurrence. In obese patients with anatomical alterations of the upper airways it is often difficult to predict success for surgical correction since obesity is a limiting factor. Therefore, the aim of the present study was to evaluate the results of tonsillectomy in a specific group of patients, i.e., obese OSAHS patients with tonsil hypertrophy. Seven OSAHS patients with moderate obesity with obstructive palatine tonsil hypertrophy were submitted to tonsillectomy. All patients were submitted to pre- and postoperative appraisal of body mass index, otorhinolaryngology examination and polysomnography. Patients' average age was 36.4 ± 10.3 years and average preoperative body mass index was 36.6 ± 6.3 kg/m². Postoperative weight did not differ significantly from preoperative weight (P = 0.27). Average preoperative apnea and hypopnea index (AHI) was 81 ± 26/h and postoperative AHI was 23 ± 18/h (P = 0.0005). Average preoperative minimum oxyhemoglobin saturation (SaO2 min) was 69 ± 14% and the postoperative value was 83 ± 3% (P = 0.038). In relation to AHI, 6 (86%) of the 7 patients studied showed a reduction of 50% in relation to preoperative level and of these, 4 (57%) presented AHI of less than 20%. Only one patient presented a reduction of less than 50% in AHI, but even so showed improved SaO2 min. Tonsillectomy treatment for OSAHS in obese patients with obstructive palatine tonsil hypertrophy caused a significant reduction in AHI, with improvement in SaO2 min. This procedure could be eventually considered as an option of treatment for obese OSAHS patients with significant tonsil hypertrophy when continuous positive air pressure therapy is not possible as the first choice of treatment.